PENERAPAN METODE MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN IPS DI KELAS IV SDN RANCAILAT 1 KABUPATEN TANGERANG - Ika Diana Putri; Zerri Rahman Hakim; M. Taufik (STKIP Subang, 2023)
For maximum learning we must develop skills or abilities as potential that we have, such as the ability to think as a means in learning to involve students in learning activities in class. This study aims to find out whether there are differences in students creative thingking abilities with the application of the Mind Mapping method in social studies class IV SD Negeri Rancailat 1 Kabupaten Tangerang. The research method used was quasi-experimental, with the research design used in the form of a Nonequivalent Control Group Design. The sample studied was class IVA students as an experimental class totaling 25 students and class IVB as a control class totaling 25 students. The analysis technique in this study was the Test-T. based on the result of the T-test calculation, obtained Thitung of 4,5814 and the Ttabel of 2,01063. Thus fulfilling the test criteria Thitung>Ttabel then Ha is accepted at a significant level 5%. Which means there are differences in students creative thingking abilities with the application of the Mind Mapping method of fourth grade elementary school students in IPSsubjects, in material (1) production, distribution and consumption economic activities (2) types of work related to lifestyle surrounding community (3) types of jobs that produce goods and service.